The Question of Identification and Individualization in the Science of Criminalistics - Balláné Füszter, Erzsébet (Magyar Rendészet, 2017)
The reconstruction of a criminal event depends on the testimony of the people involved (victim, suspect and witnesses) and the thorough examination of the available physical evidence. In answering the questions that occur during an investigation, it is mostly the specialists of criminalistics and forensic scientists that may come to our help. Identification is an essential element of criminal investigation. In criminalistics, the term refers to a complex procedure that both identifies an unknown material and also aims to unveil its origins.